O dualismo antagônico na teoria do eros em Platão e na teoria pulsional em Freud - Sales, José Josivan Bezerra de (2015)
This study aimed to perform a qualitative bibliographic research that probes Freud‟s analogy about his Pulsional Theory and the Eros of Plato Theory. For that, we choose the topic of antagonistic dualism as a similarity factor after we had observed several themes which were studied by other authors. In the first chapter we analyzed how this antagonistic dualism was shown in the theories of three original philosophers, Thales, Anaximader and Anaximenes. After, we analyzed the same topic in relation to Heraclitus‟s and Empedocles‟ theories and we studied the antagonistic dualism conceptions of soul and Eros in the compositions of Phaedo, Symposium, The Republic and Phaedrus from Plato. In the second chapter we studied present the epistemological context of the urge concept. From this point we studied Freud‟s composition and its antagonistic dualism between self-preservation and sexual drives in the First Drive Theory. We then went through the narcissistic libido and studied this opposition between life and death urges in the Second Drive Theory. In the third chapter we first started to compare the antagonistic dualism in Plato‟s and after in Freud‟s modus operandi. By trying to explain the man under a rational perspective, these philosophers couldn‟t had left the contradictory of myth and metaphysics in their theories. We then started studying the approximation made by different authors in order to understand the similarities and dissimilarities in the theory of Eros and the Libido. We concluded that the urge dualism is far from being contradictory and is a competitor and confluent in the sense of they both help each other in its own opposition. This fact allowed us to get close to three authors who point to this type of opposition: Garcia-Roza, André Green and Ivan Corrêa. So that our study is far from presenting a conclusion and it will remain open to reinforce in this opposition that generates life.